EFEKTIFITAS MODERASI BERAGAMA DALAM MENINGKATKAN SIKAP TOLERANSI DI KABUPATEN PESISIR SELATAN - Syamsarina, Syamsarina; Harahap, Samsul Bahry; Usman, Usman; Mu’arrif, Zul Ihsan (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2023)
Religious moderation is important for the harmony of every community group. So that the creation of tolerance is the goal of the state, especially the Ministry of Religion. IAIN Kerinci is one of the educational institutions that organizes community service activities based on religious moderation. The location where the KKN is implemented is in Pesisir Selatan Regency, to be precise in 4 different sub-districts. The methods used are Social Reflection, Participation Planning, Action, and Evaluation. Social Reflection by observing both directly and indirectly the condition of the village that will be occupied. Participation Planning by knowing the problems that are occurring and looking for alternatives that are in accordance with the implementation of the KKN program. Action by carrying out KKN activities based on plans that have been prepared. Evaluation by asking for suggestions and distributing questionnaires to various parties involved in implementing KKN. The evaluation results of the implementation of KKN from both Field Supervisors, Village Trustees, Students and the Community were mostly very effective.